ANALISIS YURIDIS PERLINDUNGAN HUKUM HAK KORBAN TERHADAP PEMBAYARAN RESTITUSI YANG MENJADI TANGGUNG JAWAB PELAKU PERDAGANGAN ORANG: - - ADRIAN, ADRIANUS KAPA (LPPM Universitas Putera Batam, 2023)
The more organized human trafficking crimes get, the more difficult it is for the governmentto protect victims since crimes become global, structured, and systematic. This instancehighlights the importance of conducting further research into the protection of victims fromthe crime of human trafficking. The reality that incidents of human trafficking are rising andcausing many victims to suffer in many ways, requiring legal protection for all suffering andloss suffered as a result of the illegal act of human trafficking. In this instance, the victim hasthe right to reparation, which is the duty of the trafficker. This research attempts to clarify thelegal protection of victims of human trafficking, as well as to provide feedback andsuggestions to all parties concerned. It employs normative juridical research methodologiesto investigate legal materials and concepts concerning victims' rights to compensation. Thefindings indicate that Law No. 21 of 2007 on the Abolition of the Crime of Human Traffickinggives additional assurances and legal clarity regarding the legal protection of victims' rights